Coordinated power control without AC voltage sensing and active power filtering using interlinking converter with reduced interlinking power flow in a droop controlled islanded hybrid AC‐DC microgrid. (12th January 2021) - Shravan, R. V. S. E.; Vyjayanthi, C.
Summary: An interlinking converter (IC) in a hybrid AC‐DC microgrid (HMG) is the power transfer medium between the AC and DC subgrids. This article proposes a modified control strategy of IC for carrying out the power transfer between the subgrids without sensing the AC voltages. This control strategy directly extracts the AC voltages from the gate signals used for controlling the IC. The omission of AC voltage sensing process upgrades the reliability of the system and also minimizes the size and cost of the system considerably. The paper also studies the operation of IC as an active power filter (APF) under non‐linear loading conditions, with the objective of reducing the interlinking power flow. APF using IC while carrying out power transfer between the subgrids generate high power losses. This issue is addressed by controlling the IC using the power request method, thereby ensuring a reduced power flow through the IC. In this article, the results obtained from the simulation of the HMG in MATLAB/Simulink are presented to verify effectiveness of the proposed control strategy. The results of real‐time simulations performed using OPAL‐RT (OP4500) real‐time simulator test bed are also presented to validate the potency of the proposed control strategy. Abstract : In this work, power management using power request‐based method without AC voltage sensing and active power filtering in hybrid AC/DC micro grids is carried out. Towards this, an efficient control strategy is devised to operate the interlinking converter. MATLAB Simulation and real‐time digital simulator results are presented.